Android-Based Work and Energy Physics Mobile App (WEPMA) Development - Nugroho Prasetya Adi; Muhammad Zaini (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
This research aims to produce WEPMA on feasible work and energy materials in terms of materials, media, and educator responses. The research method used is research and development (R&D), using the 4D model (Define, Design, Develop, and Disseminate). The product developed is a mobile phone-based physics learning media on business and energy material which consists of 6 main components: homepage, competency, material, simulation, quiz, and profile. The results showed that WEPMA could be used as a teaching medium in the physics subject of work and energy based on expert judgment with outstanding categories for media, materials, and educator responses.